STUDY ON INDONESIA NEW ONLINE SINGLE SUBMISSION POLICY ON ENVIRONMENTAL PERMIT ON BUSINESS IN INDONESIA - Daniel Hendrawan, Christian Andersen, Tanisa Nursyifa Dewi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
An Environmental Permit is the basis for making a Business Permit in accordance with Article 36 paragraph (1) of Law Number 32 of 2009 concerning Environmental Protection and Management. However, according to Article 32 paragraph (2) of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services or the Online Single Submission System of Environmental Permits can be committed according to Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services, this makes the existence of articles which overlaps and results in the absence of legal certainty for the community.This study shows that the legal status of the Environmental Permit as the basis for making a Business Permit or activity is in accordance with their legal relationship, which is a mandatory requirement for making a Business Permit or activity, in accordance with Law Number 32 of 2009 concerning Environmental Protection and Management and also in accordance with Law Number 12 of 2011 concerning Formation of Regulations of Laws in Indonesia . This study also addresses the responsibilities of the power holders and institutions that issue Business Permits without an Environmental Permit that causes environmental pollution by revoking permits, compensating for damages, and being responsible for making the polluted environment healthy again. Business Actors also have their own responsibilities if running a business without an Environmental Permit and if Business Actors cause environmental pollution, namely administrative responsibility, civil liability and criminal liability.